Comparison of Remission Criteria in Patients with Rheumatoid Arthritis: Results from a Smart System of Disease Management Group - Zhang Y; Du K; Feng X; Xu J; Xu P; Huang J (Dove Medical Press, 2024)
Yuqi Zhang,1,2 Keqian Du,1,2 Xiaoxue Feng,1,2 Jia Xu,1,2 Peijun Xu,1,2 Jianlin Huang1,2 1Department of Rheumatology, The Sixth Affiliated Hospital, Sun Yat-Sen University, Guangzhou, People's Republic of China; 2Biomedical Innovation Center, The Sixth Affiliated Hospital, Sun Yat-sen University, Guangzhou, People's Republic of ChinaCorrespondence: Jianlin Huang; Peijun Xu, Department of Rheumatology, The Sixth Affiliated Hospital, Sun Yat-sen University, Guangzhou, 510655, People's Republic of China, Email hjianl@mail.sysu.edu.cn; xupj@mail.sysu.edu.cnPurpose: This study aimed to compare the rates of disease remission evaluated using various remission criteria, including Boolean2.0, Boolean1.0, clinical disease activity index (CDAI), simplified disease activity index (SDAI), and disease activity score using 28 joints based on C-reactive protein (DAS28-CRP) in patients with rheumatoid arthritis (RA).Patients and Methods: A cross-sectional observational analysis was performed using data from patients with RA enrolled in a smart system of disease management group (SSDM). The clinical remission rates of RA patients estimated using the DAS28-CRP, CDAI, SDAI, Boolean1.0 and Boolean2.0 criteria were investigated. Variables were compared using the t-test, Mann-Whitney U-test, or chi-squared test. The agreement between Boolean remission and the DAS28-CRP, CDAI, or SDAI definitions of remission was assessed using McNemar's test with k coefficient of agreement.Results: A total of 5619 patients were included in the analysis. The mean age of the patients was 56.33 (± 13.01) years, with the majority being female (4491, 79.9%). The rates of remission, as assessed by Boolean2.0, Boolean1.0, DAS28-CRP, CDAI, and SDAI, were 16.6%, 9.7%, 35.2%, 9.1%, and 9.4%, respectively. Comparison with Boolean1.0 criteria revealed higher concordance between Boolean2.0 and DAS28-CRP remission and lower concordance with CDAI and SDAI, regardless of whether the analysis was conducted on the entire population or subgroups based on gender, age or disease duration. Additionally, the administration of different medications may have influenced the rate of Boolean2.0 remission.Conclusion: This study demonstrated a higher concordance between Boolean2.0 criteria and DAS28-CRP remission and a lower concordance with CDAI and SDAI when compared with Boolean1.0 remission criteria.Keywords: Boolean, clinical disease activity index, concordance, disease activity score using 28 joints, remission, simplified disease activity index